CFD Modeling of a High Enthalpy Geothermal Context - Renaud, Theo; Stebel, Michal; Verdin, Patrick; Falcone, Gioia (2018)
The promising development of highly energetic geothermal resources could considerably enhance geothermal power production worldwide. The first attempt at tapping supercritical/heated fluids was made by the Iceland Deep Drilling project (IDDP), but unfortunately a magma layer at a depth of 2,100m was encountered, and the drilling was abandoned. Yet, this drilling operation failure generated new opportunities for assessing the potential power generation close to shallow magmatic intrusions. Detailed numerical methods are required to assess the heat transfer and fluid thermodynamics at wellbore and reservoir scale at near supercritical conditions to provide production scenarios and forecasts as accurate as possible. A primary steady-state study of reservoir and wellbore heat extraction from a geothermal well near a magmatic chamber has been performed wit Computational Fluid Dynamics (CFD) techniques. Using simplified geological assumptions based on the IDDP-1 well description, a 2 axisymmetric single phase flow model was developed and its results were compared to those obtained with a full 3D CFD model. The simulated output power simulations reached 25 MW at 350°C and a wellhead pressure of 140 bars. Methodology and results from this study show that CFD techniques can be successfully used to assess geothermal energy outputs for unconventional geothermal wells and can provide details of a vapor superheated flow structure at wellbore-reservoir scale.